Reduced human activity in shallow reefs during the COVID-19 pandemic increases fish evenness. (May 2021) - China, Victor; Zvuloni, Assaf; Roll, Uri; Belmaker, Jonathan
Abstract: The COVID-19 pandemic provides a rare opportunity to examine effects of people on natural systems and processes. Here, we collected fish diversity data from coral reefs at the Israeli Gulf of Aqaba during and after the COVID-19 lockdown. We examined beach entrances to the reef, nearby shallow reefs and deeper areas exposed mostly to divers. We found that the lockdown elicited a behavioral response that resulted in elevated species richness at designated reef entrances, predominantly influenced by increased evenness without changes to total abundances. This effect was observed both at the local scale and when several beach entrances were aggregated together. Consequently, non-extractive human activities may have substantial short-term impacts on fish diversity. Our insights could help designate guidelines to manage visitor impacts on coral reefs and aid in their prolonged persistence. Highlights: Cessation of human activity resulted in changes in species richness of reef fishes. Habitats with high levels of human activity showed increased species richness during lockdown. Changes in species diversity were due to behavioral response of fish moving between habitats or reducing activity levels. Restricting human activities to few designated entrance points can minimize human disturbances on reef fishes